IMPLEMENTASI GAYA MENGAJAR DEMOKRATIS OLEH GURU KELAS DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG INKLUSIF - Popi Suranti; Ahsin Takiyudin Haniah; Harsono; Masduki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of inclusive education in elementary schools requires pedagogical practices that are able to accommodate the diversity of students’ characteristics, learning needs, and social backgrounds. In this context, a democratic teaching style is considered a relevant approach because it provides opportunities for students to actively participate, express their opinions, and take part in classroom decision-making processes. However, its implementation in Indonesian elementary schools still faces various challenges, particularly related to teachers’ awareness, school support, and understanding of the principles of inclusivity. This study was conducted to examine how classroom teachers at SD Negeri Karangsari implement a democratic teaching style and how this practice contributes to the creation of an inclusive learning environment. The objectives of this study are to describe in depth the forms of implementation of a democratic teaching style by classroom teachers, identify strategies used to support inclusivity, and analyze its impact on students’ participation and engagement in the learning process. This study also aims to reveal the supporting and inhibiting factors that affect the effectiveness of implementing a democratic approach in elementary schools. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers, the school principal, and students, as well as document analysis such as lesson plans and learning records. Informants were selected using purposive sampling, while data analysis followed the Miles, Huberman, and Saldaña model through data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation, source triangulation, and member checking. The results indicate that teachers apply a democratic teaching style by providing opportunities for students to express opinions, implementing dialogue-based learning, making joint decisions, and using differentiated instruction to meet diverse learning needs. The findings also show that the application of a democratic teaching style contributes significantly to creating an inclusive learning environment, as indicated by increased student participation, self-confidence, harmonious interactions, and the creation of an open and mutually respectful classroom atmosphere. In addition, school support, positive emotional relationships between teachers and students, and a collaborative classroom culture were identified as key factors that strengthen this practice. Meanwhile, time constraints, large class sizes, and variations in individual needs remain challenges that require further solutions. Overall, this study confirms that a democratic teaching style is a strategic approach to strengthening the implementation of inclusive education at the elementary school level.